An Investigation for causes of Centralized Governance evolution in Iran in the current century in the viewpoint of Political Geography - Ehsan Lashgari Tafreshi (دولت‌پژوهی, 2019)
After the coming of the Pahlavi regime, with the formation of nation-state in Iran, centralized governance apparatus was only continuation pattern in governing in the contemporary era. For understanding the reasons of continuity the centralized governance pattern in Iran, there have been raised many debates in the field of sociology and political science. But political processes, including the feature of governance, also affect by geographical situation and any emerging phenomenon in a country, including the features governance is basically influenced by the natural and human dimensions of country. In this regard, political geography views are against theories that believe that evolution of societies pass through the same stages. In this paper, with the descriptive-analytical approach, have been struggled to explain the most important geographic indices for continuity of centralized apparatus in Iran. A new perspective has been posed on the causes of the centralized governance emergence in Iran. Findings research reveals that the slowdown of the spatial and structural distribution of power in Iran produced from geographical factors such as increasing the share of oil revenues in generating public expenditure and developing the rendering government. Also, Inappropriate dispersal of biological resources and ecological needs has been caused more need for greater role the government in improving the viability of unplanned areas.